The problems of translating аrabic poetry - Kozhabekova, R. S. (Journal of Oriental Studies, 2016)
The article examines ways of promoting translations of Arabic poetry into Kazakh, exploring issues related to the transfer - a kind of creative thinking development of nations today and in the future.